Enhanced sensitivity of self-powered NO2 gas sensor to sub-ppb level using triboelectric effect based on surface-modified PDMS and 3D-graphene/CNT network. (September 2021) - Hong, Hoang Si; Ha, Nguyen Hai; Thinh, Dao Duc; Nam, Nguyen Hoang; Huong, Nguyen Thanh; Thi Hue, Nguyen; Hoang, Tran Vinh
Abstract: Self-powered contact electrification based flexible NO2 gas sensor has been investigated by a simple and cost-effective energy generation method at room temperature. After contact vertically surface-modified polydimethylsiloxane (PDMS) to graphene or 3D-graphene/CNT network; result mechanical energy converts into electrical energy. In relative humidity environment of 40–45%, the peak-to peak open circuit voltage were around 6.2 V and 25.4 V for graphene and 3D-graphene/CNT sample, respectively. Then a series of very-low NO2 gas concentration at ppb level systematically controlled generated-voltage at output of self-powered sensor. Thanks to larger area contact, high-efficient triboelectric effects between 3D-graphene/CNT and surface-modified PMDS, the self-powered NO2 gas sensor showed promising results in terms of high sensitivity, mechanical robust, stability and linearity. The output voltage and sensor response of 3D-graphene/CNT obtained approximately 23.1 V and 9.1% at 10 ppb NO2 . The effects of humidity on sensor response and selectivity of fabricated sensor were also investigated. The works therefore stimulate practicability and innovative approach for triboelectric nanogenerator based self-powered system towards gas sensing applications. Graphical Abstract: Self-powered NO2 gas sensor at sub-ppb level using triboelectric effects between surface-modified PMDS and 3D-graphene/CNT network ga1 Highlights: Self-powered NO2 gas sensor with sensitivity at sub-ppb level. Low detection limit (10 ppb) of NO2 gas sensor by triboelectric effects. High sensitive NO2 gas sensor due to triboelectric effects between 3D-graphene/CNT and PMDS.